Successful Treatment of a Single Giant Renal Cyst in a Newborn with Drainage and Sclerotherapy - Adriana Koenig; Anika Ménétrey; Tobias Jhala; Vincent Uerlings; Philipp O. Szavay (Georg Thieme Verlag KG, 2022)
Simple renal cysts are a scarce entity in pediatric patients and their etiology is unknown in most cases. Usually, they are monitored with ultrasound and regular follow-up of renal function. Surgical treatment is rarely indicated. We report the case of a newborn with a single giant renal cyst that could be treated successfully with drainage and sclerotherapy. Single giant renal cysts require careful investigation and monitoring. In cysts without communication to the pelvico-caliceal system, sclerotherapy by instillation of doxycycline is a therapeutic option.